Unravelling English Language Space Constituted in Model School Construction in Nepal - Devkota, Kamal Raj (Education and Development, 2019)
School Sector Development Plan (SSDP, 2016-2023) has envisaged the establishment and operation of ‘model schools’ to demonstrate improved management and teaching-learning therein. One thousand secondary schools representing all provinces and districts are planned to be developed as model schools, and three hundred and five have already been selected for initiating the project in 2017/18. Model School Guideline has been developed in the framework of SSDP; and in accordance with that, the selected schools are provided with certain financial support for building infrastructure, improving classroom delivery and instructional activities, and bringing efficiency in school management. Based on the fieldwork in four sample schools of Nepal, this study has unraveled how these ‘model’ schools have understood, experienced and enacted with English language space (ELS) in the course of model school construction. The analysis of the field data especially derived from school observation, qualitative research interviews and Focus Group Discussions with teachers, School Management Committee members and students unpacks how English language, which is often defined as the key for students’ and parents’ choice of school, is equally associated with confusion and ambivalence in the construction of model schools in Nepal. The analysis shows that the confusion and ambivalence concentrate around three major constructs: ELS as instrumental to school sustainability, ELS as a conflicting zone, and ELS as the educultural reality in the current educational discourses.